Water and Sewage Management in The Districts of Lubuskie Voivodeship, Poland - Płuciennik-Koropczuk, Ewelina; Myszograj, Sylwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Since 1991, Poland has been taking steps to organize the country's wastewater management in order to meet the requirements of Council Directive 91/271/EEC. The current goals to achieve the said requirements are set in the VI update of the National Urban Wastewater Treatment Program (KPOŚK) and has to be achieved to 2027. The article presents the status of water and wastewater management in the districts of Lubuskie Voivodeship, Poland in 2021, in relation to year 2017. The degree of water supply and sewerage system, as well as wastewater systems management in individual agglomerations of Lubuskie Voivodeship are defined.
Keywords: water system supply; WWTP; sewage system; rural areas; urban area; Lubuskie voivodship; zasilanie sieci wodociągowej; oczyszczalnia ścieków; kanalizacja; obszary wiejskie; obszary miejskie; województwo lubuskie